Effectiveness of Animated Video on Tooth Brushing Skills of Children with Down Syndrome - Lu'lu'a Fadlila Zain; Indah Lestari Vidyahayati; Ira Anggar Kusuma; Tira Hamdillah Skripsa (Faculty of Medicine, Diponegoro University, 2026)
Background: Down syndrome is a congenital disorder caused by chromosome 21 failing to separate during cell division, causing impaired physical and mental development. Children with Down syndrome often have difficulty taking care of themselves, including brushing their teeth. This can increase the risk of developing dental and oral health problems. Education using animated video media can increase children's attention so that the material presented is easy to understand. Therefore, animated videos are expected to improve the brushing skills of children with Down syndrome.Objective: To determine the effectiveness of animated video on tooth brushing skills of children with Down syndrome at 6 Special Schools in Semarang City.Methods: This study was a quasi-experimental non-equivalent control group design involving 48 children with Down syndrome at 6 Special Schools in Semarang City as the sample. The sample was divided into two groups, each consisting of 24 children. One group received intervention using animated videos, while the other group received intervention using conventional media (dental phantom). Assessment of oral hygiene skills was conducted before and after the intervention using observation sheets that had undergone validity and reliability testing. Data analysis was performed using paired t-test and independent t-test.Results: The results showed a significant difference in the average tooth brushing skills of children with Down syndrome (p<0.001) between the animated video and dental phantom media groups Conclusion: Oral health intervention using animated video media is effective in improving tooth brushing skills of children with Down syndrome at 6 Special Schools in Semarang City.